(3Yed GdSGYGJ GdeHShWI HGdgfOSI aj Ci Ebdje CQOJs - (3GdMSf Hf eMeO Hf GdUHGM GdHRGQ GdRYaQGfqj GdHZOGOj, GHf GdnqUnqHGM,J (B259 (3g` s
(3ChdgG (B:s
(3hef gPg GdCdg fSJNQL SYg eTQb GdHQhL hebOGQ CfgGQgG hCReGJ cMd ef fgGQ gPg GdHQhL s
(3BNQgG (B:s
(3hGdYed ceG aYdfG ai HQL GdLOi dSGYGJ GdSQWGf cdgG , hbO GdYed s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B212 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B284s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B861 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B67 s
(3eUOQ GbJfGA GdCUd (B:s
(3CjGUhajG (B(48309) s
Keywords: (3GdQjGVjGJs